2015
DOI: 10.1002/bmc.3605
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive LC‐MS/MS method for the determination of linarin in small‐volume rat plasma and tissue samples and its application to pharmacokinetic and tissue distribution study

Abstract: A rapid and sensitive LC-MS/MS method was developed for the determination of linarin in small-volume rat plasma and tissue sample. Sample preparation was employed by the combination of protein precipitation (PPT) and liquid-liquid extraction (LLE) to allow measurement over a 5-order-of-magnitude concentration range. Fast chromatographic separation was achieved on a Hypersil Gold column (100 × 2.1 mm i.d., 5 µm). Mass spectrometric detection was achieved using a triple-quadrupole mass spectrometer equipped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It has also been reported that linarin possesses analgesic, antipyretic [ 46 ], and neuroprotective activities [ 47 ], and showed a protective effect against d -glactosamine/LPS-induced fulminant hepatic failure [ 48 ]. Furthermore, a tissue distribution study of linarin has revealed that it was rapidly and widely distributed in the heart, liver, spleen, lung, kidney, brain, muscle, stomach, small intestine, epididymis, pancreas, and bladder of rats after intragastric administration [ 49 ]. Since there was little data on the anti-inflammatory mechanism of linarin [ 50 ], the present study explored its involvement in the anti-inflammatory action of the MHP extract.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that linarin possesses analgesic, antipyretic [ 46 ], and neuroprotective activities [ 47 ], and showed a protective effect against d -glactosamine/LPS-induced fulminant hepatic failure [ 48 ]. Furthermore, a tissue distribution study of linarin has revealed that it was rapidly and widely distributed in the heart, liver, spleen, lung, kidney, brain, muscle, stomach, small intestine, epididymis, pancreas, and bladder of rats after intragastric administration [ 49 ]. Since there was little data on the anti-inflammatory mechanism of linarin [ 50 ], the present study explored its involvement in the anti-inflammatory action of the MHP extract.…”
Section: Discussionmentioning
confidence: 99%
“…Protein precipitation (PPT) is widely used in biological analysis, especially for high-throughput screening, due to its fast, simple, and cost-efficient characteristics (Feng, Liu, Wang, & Di, 2016;Zhao et al, 2019). Moreover, PPT often provides higher recovery of analytes when compared with solid-phase extraction (SPE) and liquid-liquid extraction (LLE) after optimizing the most appropriate precipitation reagent (Rathod et al, 2017;Wang et al, 2018).…”
Section: Conventional Pretreatment Methodsmentioning
confidence: 99%
“…However, one of our previous studies revealed that linarin shows low bioavailability (0.47%) after oral administration, which suggests that linarin could be extensively metabolized after oral administration, and the metabolites of linarin could still show various pharmacological activities [11]. Acacetin, apigenin, and p -hydroxy benzaldehyde (Figure 1) have been identified as the metabolites of linarin [12].…”
Section: Introductionmentioning
confidence: 99%
“…We found that these three metabolites showed a protective effect against severe d -GalN-induced hepatic failure in rats (data not shown). Up to now, the pharmacokinetic study of linarin had been extensively reported [11,13,14,15,16]; however, no pharmacokinetic study of its metabolites is available. Thus, further studies to elucidate the pharmacokinetics and liver tissue distribution of linarin and its active metabolites are still needed and will be helpful for a better understanding of the pharmacological effects of linarin.…”
Section: Introductionmentioning
confidence: 99%